Analisis Pengaruh Nilai Tukar, Inflasi, Jumlah Uang Beredar, Utang Luar Negeri, dan Produk Domestik Bruto terhadap Cadangan Devisa Di Indonesia - Stefani, Elisa; Huda, Syamsul; Wahed, Mohammad (Ridwan Institute, 2021)
The research was conducted with the aim of knowing the influence of exchange rates, inflation, money supply, external debt, and gross domestic product on foreign exchange reserves in Indonesia in the quarter of 2016 to 2020. Secondary data in this study was obtained through the website of the Central Bureau of Statistics and Bank Indonesia. This study used quantitative methods and used Multiple Linear Regression Analysis with Ordinary Least Square (OLS) model. It can be concluded that the exchange rate has a negative and significant effect on foreign exchange reserves, the amount of money supply and external debt has a positive and significant effect on foreign exchange reserves, while for inflation and external debt has a positive but insignificant influence on foreign exchange reserves.